Prevalence of Breast Cancer in different geographical regions: A Retrospective Study from Central Nepal - Sapkota, Ganga; Poudel, Bishwa Ram; Mallik, Dipendra Kumar; Wagle, Bhawna; Dhakal, Sunil; Bhandari, Sapana (Nepalese Journal of Cancer, 2022)
Background: Breast cancer is the second most common malignancy among Nepalese women with prevalence of 28.5 per 100,000 population. In Nepal due to lack of uniform health resources and awareness, breast cancer cases reporting is different in three geographical regions. This study aims to look at the difference in prevalence of breast cancer in different geographical regions. Materials and Methods: A single center descriptive retrospective study to analyze the prevalence of breast cancer in different geographical regions among patients visiting BPKMCH from January 2014 to December 2018 was designed and patients’ information available at medical record were obtained. Analysis was completed with SPSS Statistics. Results: During the period of 5-year total 2115 cases of breast cancer were seen at the Department of Surgical Oncology at BPKMCH. These cases comprised of 2052 female and 63males. The mean age of presentation was 48 years. Maximum number of cases 65% (1376) were from terai region of Nepal. Conclusions: This study provides clue regarding higher cases of breast cancer among individuals from terai region of Nepal.